Attenuating M-current suppression in vivo by a mutant Kcnq2 gene knock-in reduces seizure burden, and prevents status epilepticus-induced neuronal death and epileptogenesis - Greene, Derek L. (Epilepsia, 2018)
OBJECTIVES: The M-current is a low threshold voltage-gated potassium current generated by Kv7 subunits that regulates neural excitation. Importantly, M-current suppression, induced by activation of Gq-coupled neurotransmitter receptors, can dynamically regulate the threshold of action potential firing and firing frequency. Here we sought to directly examine whether M-current suppression is involved in seizures and epileptogenesis. METHODS: Kv7.2 knock-in mice lacking the key PKC phosphorylation acceptor site for M-current suppression were generated by introducing an alanine substitution at serine residue 559 of mouse Kv7.2, mKv7.2(S559A). Basic electrophysiological properties of the M-current between wildtype and Kv7.2(S559A) knock-in mice were analyzed in primary cultured neurons. Homozygous Kv7.2(S559A) knock-in mice were used to evaluate the protective effect of mutant Kv7.2 channel against chemoconvulsant-induced seizures. In addition, pilocarpine-induced neuronal damage and spontaneously recurrent seizures were evaluated after equivalent chemoconvulsant-induced status epilepticus was achieved by coadministration of M-current specific channel inhibitor, XE991. RESULT: Neurons from Kv7.2(S559A) knock-in mice showed normal basal M-currents. Knock-in mice displayed reduced M-current suppression when challenged by a muscarinic agonist, oxotremorine-M. Kv7.2(S559A) mice were resistant to chemoconvulsant-induced seizures with no mortality. Administration of XE991 transiently exacerbated seizures in knock-in mice equivalent to those of wildtype mice. Valproate, which disrupts neurotransmitter-induced M-current suppression, showed no additional anticonvulsant effect in Kv7.2(S559A) mice. After experiencing status epilepticus, Kv7.2(S559A) knock-in mice did not show seizure-induced cell death nor spontaneous recurring seizures.